FAKTOR-FAKTOR YANG MEMPENGARUHI PENGGUNAAN KONTRASEPSI DAN HAK REPRODUKSI PEREMPUAN PADA KELUARGA AKSEPTOR KB DI KELURAHAN MACCORAWALIE KAB. PINRANG - Sitti Hardiyanti; Idham Irwansyah (PREDESTINATION: Journal of Society and Culture, 2021)
The results of this study indicate that the driving factors for acceptors to use family planning are, first, external factors, which are driving factors that arise outside of the condition of a family where the role of the government and related institutions plyas an active role in various outreach socializations and the second is internal factors, factors based on in a situation or condition that exists in one family, namely because you want to delay pregnancy, due to economic factors where the acceptors in the family have a low economic level and work factors where the acceptors are busy in their, apart from that, the driving factor for the acceptors to do family planning is to keep their distance births because families prefer to regulate the birth spacing of children and participate in family planning programs to reduce population growth rates. From the research result it can also be concluded that the position of women in reproductive rights in choosing contraceptive methods is based on a joint decision between husband and wife, but there is also a decision made by one party only.